Thermal Performance Of Multi Piezoelectric Fan For Electronic Cooling Application Using 3-D Dynamic Mesh - Abdullah @ Harun, Muhammad Khalil (2012)
Piezoelectric fan (hereafter name as piezofan) can be manipulated to generate airflow for cooling microelectronic devices. Its outstanding features include noise-free operation, low power consumption and suitability for confined spaces. The main aim of the present study was to investigate the performance of an oscillating piezofan through the use of numerical modeling. The commercial CFD software Fluent 6.3.2TM was used to solve the Reynolds Averaged Navier Stokes (RANS) equations with the consideration of shear stress transport (SST) k- model. The harmonic motion of the first mode in the deforming beam (piezofan) was developed using C language, and was set under dynamic mesh option with the help of a user defined function (UDF).